Cartography of violences in municipal schools of Santiago, Chile. A situated case study (Cartografía de las violencias en las escuelas municipales de Santiago de Chile. Un estudio de caso). Issue 2 (3rd April 2022) - Moscoso-Flores, Pedro; Azócar, Patricio; Jert, Andrea
ABSTRACT: This text addresses the main results obtained from an investigation focused on the description and analysis of school violences within the context of two emblematic municipal high schools in the central Santiago district in Chile. Through a transdisciplinary qualitative methodology, which we have stated as cartographies of violences, we develop a stratified analysis matrix with the aim of proposing an interpretation regarding the violences that arise within educational institutions within the framework of the recent educational paradigm of inclusion, and the ways by which they compose and are part of the socialization strategies of educational stakeholders in situated educational contexts. We will conclude our analysis with the presentation of certain critical nodes composed by the integration of strata, thus offering a specific vision regarding the processes of school coexistence and socialization in each institution.